MBRS-27. EXOSOMES CARRY DISTINCT miRNAs THAT DRIVE MEDULLOBLASTOMA PROGRESSION. (4th December 2020) - Jackson, Hannah K; Linke, Franziska; Kerr, Ian; Coyle, Beth
Abstract: INTRODUCTION: Extracellular vesicles (EVs) represent an ideal source of functional biomarkers due to their role in intercellular communication and their ability to protect cargo, including RNA, from degradation. The most investigated EV's are exosomes, nanovesicles secreted by all cell types and able to cross the blood-brain-barrier. Here we characterised the RNA of exosomes isolated from medulloblastoma cell lines, with the aim of investigating exosomal RNA cargo as potential functional biomarkers for medulloblastoma. METHODS: Exosomes derived from a panel of matched (original tumour and metastasis) medulloblastoma cell lines were isolated and characterised by NanoSight, electron microscopy, western blotting and Nanoscale flow cytometry. Exosomal miRNA and mRNA from our matched cell lines and foetal neuronal stem cells, which were used as a normal control, were analysed by RNA-sequencing technology. RESULTS: Based on hierarchical clustering, malignant derived exosomes were distinctly separated from normal control exosomes. miRNA profiling revealed several established oncomiRs identified in our malignant derived exosomes compared to control samples. Using interaction pathway analysis, we identified that our malignant exosomes carry numerous miRNAs implicated in migration, proliferation, cellular adhesion and tumour growth. Several previously identified oncomiRs were also identified to be present at higher levels in metastatic exosomes compared to primary and normal, including hsa-miR-455-3p and hsa-miR-92a-3p. CONCLUSION: This study shows that exosomes from MB cells carry a distinct miRNA cargo which could enhance medulloblastoma progression. The use of circulating exosomes as markers of metastatic disease could be an innovative and powerful non-invasive tool.